PENYULUHAN MASYARAKAT PENTINGNYA PENDIDIKAN INKLUSIF BAGI ANAK BEREBUTUHAN KHUSUS DIDESA PETAPAHAN KECAMATAN GUNUNG TOAR KUANSING - Merlina Sari; Akhmad Suyono; Novia Nazirun (Bajang Institute, 2022)
Inclusive Education for Children in Need and the emotion that all children have access to education that is affordable, effective, relevant and appropriate in their area of ​​residence, provokes all parties to create a conducive learning environment so that all children are involved in the learning process. So, inclusiveness in education is a process increasing student participation and reducing their separation from the culture, curriculum and local school community. Students with special needs can be accepted and study in public/regular schools.